Dirty South Feminism: The Girlies Got Somethin’ to Say Too! Southern Hip-Hop Women, Fighting Respectability, Talking Mess, and Twerking Up the Dirty South - Adeerya Johnson (MDPI AG, 2021)
Within southern hip-hop, minimal credit has been given to the Black women who have curated sonic and performance narratives within the southern region. Many southern hip-hop scholars and journalists have centralized the accomplishments and masculinities of southern male rap performances. Here, dirty south feminism works to explore how agency, location, and Black women’s rap (lyrics and rhyme) and dance (twerking) performances in southern hip-hop are established under a contemporary hip-hop womanist framework. I critique the history of southern hip-hop culture by decentralizing male-dominated and hyper-masculine southern hip-hop identities. Second, I extend hip-hop feminist/womanist scholarship that includes tangible reflections of Black womanhood that emerge out of the South to see how these narratives reshape and re-inform representations of Black women and girls within southern hip-hop culture. I use dirty south feminism to include geographical understandings of southern Black women who have grown up in the South and been sexually shamed, objectified and pushed to the margins in southern hip-hop history. I seek to explore the following questions: How does the performance of Black women’s presence in hip-hop dance localize the South to help expand narratives within dirty south hip-hop? How can the “dirty south” as a geographical place within hip-hop be a guide to disrupt a conservative hip-hop South through a hip-hop womanist lens?